Research on the education of Asian and Pacific Americans. volume 1 - Park, Clara C., 1944-; Goodwin, A. Lin; Lee, Stacey J., 1962- (Research on the education of Asian and Pacific Americans ;, 2001)
As the first volume in a series sponsored by SIG-Research on the Education of Asian and Pacific Americans of the American educational Research Association and California Association for Asian and Pacific American Education, this book sheds important light on the educational needs of Asian and Pacific American students in k- college. Each chapter illuminates the unique issues confronting Asian and Pacific Americans and provides crucial information necessary to understand how Asian and Pacific American students learn and how educational practitioners should work with Asian and Pacific students. This body of knowledge can inform researchers and practitioners, as well as policy makers, of effective instruction for Asian and Pacific American students at all levels. The series intends to be a national voice for the education of Asian and Pacific Americans, and provide an integrated view of new knowledge in the field of Asian and Pacific American education from scholar - practitioners' perspectives.